ECONOMIC AND POLITICAL MARKETS - Prokopijević, Miroslav L (Politeia, 2017)
This paper deals with the question of whether there is an analogy between the economic and political market. The quest is conducted in three parts. Part one shows that the analogy between the economic and political market holds, as there are many important similarities between the two markets. Part two demonstrates that some vital theorems, which hold on the economic market, do not hold on the political market. This is demonstrated in the case of the Coase’s theorem. Finally, part three deals with the market and state failure. After discussion of the topic in the three parts, one may conclude that the analogy between two markets works, but that they function with significant differences. The differences are induced via different definitions of property rights, the character of the output, the system of incentives and the enforcement of contract. In a word, the political market is less perfect than the economic one, but it is a market.
Keywords: state failure; market failure; Coase’s theorem; political market; economic market